Divergent responses of the coral holobiont to deoxygenation and prior environmental stress - Swaminathan, Sara D.; Meyer, Julie L.; Johnson, Maggie D.; Paul, Valerie J.; Bartels, Erich; Altieri, Andrew H. (Frontiers in Marine Science, 2024)
Ocean deoxygenation is intensifying globally due to human activities – and is emerging as a grave threat to coral reef ecosystems where it can cause coral bleaching and mass mortality. However, deoxygenation is one of many threats to coral reefs, making it essential to understand how prior environmental stress may influence responses to deoxygenation. To address this question, we examined responses of the coral holobiont (i.e., the coral host, Symbiodiniaceae, and the microbiome) to deoxygenation in corals with different environmental stress backgrounds. We outplanted Acropora cervicornis fragments of known genotypes from an in situ nursery to two sites in the Florida Keys spanning an inshore-offshore gradient. After four months, fragments from the outplanted corals were transferred to the laboratory, where we tested differences in survivorship, tissue loss, photosynthetic efficiency, Symbiodiniaceae cell density, and coral microbiome composition after persistent exposure to one of four oxygen treatments ranging from extreme deoxygenation (0.5 mg L-1) to normoxia (6 mg L-1). We found that, for the short duration of exposure tested in this study (four days), the entire coral holobiont was resistant to dissolved oxygen (DO) concentrations as low as 2.0 mg L-1, but that the responses of members of the holobiont decoupled at 0.5 mg L-1. In this most extreme treatment, the coral host showed decreased photosynthetic efficiency, tissue loss, and mortality, and lower Symbiodiniaceae densities in a bleaching response, but most microbial taxa remained stable. Although deoxygenation did not cause major community shifts in microbiome composition, the population abundance of some microbial taxa did respond. Site history influenced some responses of the coral host and endosymbiont, but not the coral microbiome, with corals from the more stressful inshore site showing greater susceptibility to subsequent deoxygenation. Our study reveals that coral holobiont members respond differently to deoxygenation, with greater sensitivity in the coral host and Symbiodiniaceae and greater resistance in the coral microbiome, and that prior stress exposure can decrease host tolerance to deoxygenation.